EFEKTIVITAS PERENDAMAN BENIH DALAM AIR PANAS TERHADAP DAYA KECAMBAH DAN PERTUMBUHAN BIBIT ADAS (Foeniculum vulgare Mill) - Riya Wahyu Sriwigati; Libria Widiastuti; Mohamad Ihsan (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2021)
This study aims to determine the effect of submersion seeds in hot water and submersion time on the viability of fennel seeds and growth of fennel seeds (Foeniculum vulgare Mill). This research was conducted from October to December 2020, in Manggung Village RT 02 RW 04 Sukorejo Village, Musuk District, Boyolali Regency. Altitude ± 800 m asl. This study uses an environmental design in the basic pattern of Completely Randomized Design (CRD) arranged factually with 2 (two) factors repeated 3 (three) times. The first factor is submersion seeds in hot water, which consists of three levels (P1: 50ºC, P2: 60ºC, and P3: 70ºC). The second factor was the submersion time which consisted of 3 kinds of treatments (W1: 10 minutes, W2: 15 minutes, and W3: 20 minutes). The observation parameters consisted of the number of seeds germinating, germination capacity, plant height, number of leaves, root length, and weight of fresh seeds. The results showed that: Submersion treatment with hot water had a significant effect on the number of germinated seeds. And had a very significant effect on germination, plant height, number of leaves, root length, and weight of fresh seeds. The treatment of submersion time had a significant effect on the parameters of the number of seeds germinated and the germination capacity and had no significant effect on other parameters. The combination of P2W1 treatment (submersion with hot water temperature of 60°C and submersion time for 10 minutes) was able to break the dormancy of fennel seeds well until they reached 100% germination. The P x W treatment interaction showed no significant effect on other parameters.